SUSTAINABLE HRM PRACTICES AND INNOVATION IN HEALTHCARE SMES: MEDIATING ROLE OF GREEN INNOVATION USING PLS-SEM ANALYSIS - Masood, Rana Zehra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores how sustainable Human Resource Management (HRM) practices influence business performance in healthcare SMEs, with green innovation acting as a mediating variable. Employing PLS-SEM, data was collected from 200 managers in healthcare SMEs across India. The findings show that green recruiting and selection, as well as green training and development, significantly enhance on sustainable business performance. Additionally, green innovation has been found to mediate the relationship between sustainable HRM practices and business performance, underscoring its critical role in driving organizational sustainability. These findings are consistent with current literature and highlight the strategic importance of incorporating environmental sustainability into HRM practices. For practitioners, the study offers valuable insights into designing and implementing green HRM strategies to achieve both environmental and business goals. The research highlights the need for healthcare SMEs to adopt sustainable HRM practices to stay competitive and compliant with regulatory standards, thereby ensuring long-term success. Future research should consider longitudinal studies, diverse industrial contexts, and broader dimensions of sustainable HRM to further validate and expand upon these findings.